Secured wireless LAN using IPSec case study in Jabatan Agama Islam Selangor (JAIS) / Rozita Masiran - Masiran, Rozita (Faculty of Information Technology and Quantitative Sciences, 2006)
Actually this research is to implement IPSec in JAIS because of the problem with current implementation using MAC address. This MAC address system will be cause of MAC address spoofing by an unauthorized users or attackers that want to access internet (WLAN) without permission in JAIS area. aims of this research are to secure against WLAN and improved the current implementation using MAC address system. After the implementation IPSec in JAIS we can see it is better than MAC address system because the data will be encrypted with IPSec. Clients and gateway has successful negotiate IPSec and the connection between them is secure at all. Other than that IPSec can be also to secure connection between two internet host and network traffic in JAIS. This can make the unauthorized user and attackers difficult to vulnerable internet access (WLAN) in JAIS. Hopeless this project will help the network administrator in JAIS to secure their WLAN.